Design, synthesis and evaluation of cytotoxic, antimicrobial, and anti-HIV-1 activities of new 1,2,3,4-tetrahydropyrimidine derivatives - Nima Razzaghi-Asl; Mahsa Kamrani-Moghadam; Behzad Farhangi; Rouhollah Vahabpour; Rezvan Zabihollahi; Saghi Sepehri (Wolters Kluwer Medknow Publications, 2019)
A series of new 1,2,3,4-tetrahydropyrimidine (THPM) derivatives were designed and synthesized within a one-pot three component Biginelli reaction. The structures of compounds were characterized by FT-IR, 1H- NMR, mass spectroscopy, and elemental analysis. All synthesized derivatives were screened for their cytotoxic, antimicrobial, and anti-HIV activites. Due to significant cytotoxic and antimicrobial effects of 1,2,3,4-THPM scaffold, in this study, cytotoxic and antimicrobial activities of synthesized derivatives were evaluated on two cell lines and four bacterial strains. Compounds 4e and 4k showed highest cytotoxic activity against HeLa and MCF-7 cell lines. In addition, 4c and 4d were most active against MCF-7 and HeLa cell lines, respectively. Among the compounds, 4e revealed high antimicrobial activity against four strains. According to the results, 4e possessing m-bromophenyl group at C-4 position of THPM exhibited the highest cytotoxic and antimicrobial effects. Also, all the newly synthesized compounds were evaluated for their anti-HIV-1 assay. Compounds 4l and 4a indicated remarkable anti-HIV-1 activity. It is concluded from cytotoxic, antimicrobial, and anti-HIV-1 activities that the 1,2,3,4-tertahydropyrimidines may serve as hit compounds for development of new anticancer small-molecules.